2018
DOI: 10.1007/s00253-018-9513-4
|View full text |Cite
|
Sign up to set email alerts
|

A recombinant multi-epitope peptide vaccine based on MOMP and CPSIT_p6 protein protects against Chlamydia psittaci lung infection

Abstract: Chlamydia psittaci is an obligate intracellular pathogen with a broad host range that can lead to severe infectious disease by transferring from birds to humans. Vaccination has been considered the best way to prevent chlamydial infection; nevertheless, there is currently still no commercially available vaccine that can inhibit the spread of C. psittaci. In previous study, major outer membrane protein (MOMP) of C. psittaci was confirmed to be an appropriate candidate antigen for limiting C. psittaci respirator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 40 publications
1
15
0
Order By: Relevance
“…Our results also show GrpE vaccination in the presence of FCA could induce readily detectable Th1 responses; however, there wasn't increased inflammation in response to the infection or reduced pathological changes of the infected site. FCA are known to enhance the immunogenicity of the immunogen, play an immune regulation role, and increase the immune effect of the antigen, which can modulate immune cells and enhance humoral and cellular immune responses in the host (22,46,47). So we conclude that the GrpE protein in the presence of FCA may induce protective Th1 immune response in mice and be considered as an effective vaccine against U. urealyticum infection.…”
Section: Discussionmentioning
confidence: 70%
“…Our results also show GrpE vaccination in the presence of FCA could induce readily detectable Th1 responses; however, there wasn't increased inflammation in response to the infection or reduced pathological changes of the infected site. FCA are known to enhance the immunogenicity of the immunogen, play an immune regulation role, and increase the immune effect of the antigen, which can modulate immune cells and enhance humoral and cellular immune responses in the host (22,46,47). So we conclude that the GrpE protein in the presence of FCA may induce protective Th1 immune response in mice and be considered as an effective vaccine against U. urealyticum infection.…”
Section: Discussionmentioning
confidence: 70%
“…Computational analysis for B-and T-cell epitopes within the Chlamydia MOMP have been performed for many different Chlamydia species 34,35 including C. pecorum 36 . These predictions identified B-cell and T-cell epitopes within both conserved and variable domains of the MOMP.…”
Section: Discussionmentioning
confidence: 99%
“…Further, it has been demonstrated that multi-epitope combined vaccine induce stronger CTL responses compared to those induced by a single-epitope vaccine by enhancing cellular immunity and releasing immune tolerance [29]. The cellular and humoral responses generated by the multi-epitope vaccines are highly speci c with increased cytokines production [84][85][86]. A multi-epitope vaccine developed with such precautions can thus become a powerful tool in the battle against viral infections [87].…”
Section: Discussionmentioning
confidence: 99%